The use of Lapita pottery: Results from the first analysis of lipid residues. (February 2018) - Leclerc, Mathieu; Taché, Karine; Bedford, Stuart; Spriggs, Matthew; Lucquin, Alexandre; Craig, Oliver E.
Abstract: Biomolecular and isotopic characterisation of absorbed organic residues have been performed on eight dentate-stamped and two plain Lapita potsherds from the site of Teouma, in Vanuatu. Lipid profiles associated with decorated pots are homogenous, suggesting that similar food types or mixtures of food types were placed in these vessels. This suggests a high degree of consistency in the use of Lapita decorated pots, irrespective of the morphological and stylistic variation of these vessels. Data obtained from single-compound isotope analysis are also not consistent with marine resources as potential food sources for Lapita vessels. The absence of such commonly consumed, ubiquitous and easily accessible resources in Lapita vessels suggests that these pots were not manufactured to be used for ordinary occasions and day-to-day food consumption. This is the first time tangible data related to the use of these vessels are provided to support this claim in addition to contextual inferences. Highlights: Organic residue analysis of Lapita pottery from Teouma (2940–2710 cal BP), Vanuatu. Lipid profiles from decorated pots are homogenous. Data are not consistent with marine resources as potential food sources. Results suggest these pots were not manufactured to be used for ordinary occasions.